Investigation of displacement and jet ventilation systems applied in an ice rink. (1st June 2022) - Lin, Wenyu; Liu, Xiaohua; Zhang, Tao; Zhou, Ziqi
Abstract: Ice rinks are large space buildings with a unique required indoor environment and high energy consumption. On-site measurements are carried out in two professional indoor ice rinks to investigate the vertical temperature and humidity distributions with jet ventilation system and displacement ventilation system. Jet ventilation achieves a more uniform vertical distribution, while stratification is observed at the height of the baffle around the competition field with ground displacement ventilation. A verified CFD (Computational Fluid Dynamics) model established based on the measured data is utilized to analyze the indoor thermal environment. It is demonstrated that the heat and moisture transferred from the view stand consumed 42% of the cooling capacity and 83% of the dehumidification capacity in the case of jet ventilation. A better decoupled zoning control effect is obtained with displacement ventilation, with the consumed cooling and dehumidification capacities 54% and 51% lower. The present study is valuable for optimizing the ventilation system and energy conservation in ice rinks. Highlights: Indoor thermal environment of two professional ice rinks is measured. A CFD (Computational Fluid Dynamics) model is established and verified. Vertical temperature and humidity distributions with different ventilation systems are investigated. Heat and moisture migration between the competition field and the view stand are analyzed. Displacement ventilation achieves a higher energy utilization efficiency than jet ventilation.